Highly dispersed BiOCl decahedra with a highly exposed (001) facet and exceptional photocatalytic performance. Issue 33 (14th August 2020) - Bao, Liang; Yuan, Yong-Jun
Abstract : BiOCl decahedra with octagonal 110 and 100 oblique facets were hydrothermally synthesized via a simple hydrothermal method, achieving a high degradability of 98% for RhB after 6 min of irradiation. Abstract : BiOCl has been identified to be a promising photocatalyst for the rapid photodegradation of organic pollutants, but its practical application was restricted by its limited photocatalytic activity. In this work, a highly reactive BiOCl decahedron photocatalyst with an exposed (001) facet was successfully hydrothermally synthesized via a simple hydrothermal method using bismuth nitrate (Bi(NO3 )3 ·5H2 O) and ammonium chloride (NH4 Cl) as raw materials. By adjusting the dosage of NH4 Cl, the BiOCl nanoplates transformed from hexahedra with quadrilateral 110 oblique facets to decahedra with octagonal 110 and 100 oblique facets. As compared to the original BiOCl nanoplates, decahedral BiOCl possesses much more oxygen-enriched surfaces and a narrowed bandgap, resulting in enhanced photocatalytic performance. The decahedral BiOCl photocatalyst achieves a high degradability of 98% for the photodegradation of RhB after 6 min of irradiation, which is much faster than that of a hexahedral BiOCl sample.